Analisis Perhitungan dan Pelaporan Pajak Penghasilan Badan Pasal 25 Pada Pt Xyz - Cindea Corycha Putri; Rama Gita Suci (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research was made to analyze the calculation and reporting of PPH Article 25 carried out by the Accounting Services Office for PT XYZ as a client who has given confidence to the Accounting Services Office to handle the bookkeeping as well as taxation. By using sec-ondary data, researchers retrieved company financial report data in the form of a 2022 commercial profit and loss report which was used to analyze the company's Article 25 PPH calculations. The analytical method used is descriptive qualitative method. Based on the research conducted by the author, the conclusion is that it is very important for a company to understand bookkeeping and taxation in a business, especially for Taxable Entrepreneurs (PKP), and Service Offices have properly and correctly calculated and reported Corporate Income Tax, namely based on Law no. 36 of 2008, and has followed the Director General of Taxes Regulations regarding changes to the 2022 tax rate.